Dental demographics and metrics of oral diseases in the ageing Australian population. (March 2015) - Hopcraft, MS
Abstract: One of the biggest challenges currently facing the dental profession in Australia is the provision of quality and timely dental care to the elderly. Adults aged 65+ years are an exponentially growing section of the community with rapidly changing dental needs, thanks in part to improvements in oral health over the past 60 years that have resulted in a dramatically decreased rate of edentulism and subsequently an increased number of teeth present. This is a challenge not only for the public dental services, but also public health policy makers, private dental practitioners, professional organizations and dental education providers. It is an issue that crosses a range of dental care providers, not only dentists but also dental prosthetists and dental hygienists, whose role in the provision of dental services has been slowly growing in Australia. Furthermore, with evidence of links between oral and systemic health, this issue has significant impacts for the broader health system.